Produção e qualidade de cultivares de alface americana em função do espaçamento de plantio - Medeiros, Felipe Bruno Araújo de (2015)
The lettuce when grown at high temperature and light conditions, fails to express all their genetic potential, with a reduction of the cycle and advance the reproductive stage. These conditions contribute to low productivity and lower quality of this vegetable. In order to assess the quality and yield performance of lettuce cultivars as a function of planting spacing, an experiment was conducted from August to October 2014, in Horta's Departamento de Ciências Vegetais, in Universidade Federal Rural do Semi-Árido, Mossoró/RN. The experimental design was a randomized complete block design with four replications in a factorial 3 x 4. The treatments consisted of the combination of three lettuce cultivars (Amelia, Angelina and Taina) and four planting spacing (15 x 15 cm, 20 x 20 cm, 25 cm and 30 x 25 x 30 cm). Production and quality characteristics were evaluated: average plant height (cm), medium plants diameter (cm), number of leaves per plant, fresh weight of aerial parts (g plant-1), dry weight of shoots (g plant -1), productivity (t ha-1), soluble solids (%), titratable acidity (%), soluble solids / titratable acidity, pH and total soluble sugars (%). The cultivars showed similar yields, with an average of 9,58 t ha-1. The reduction in planting spacing resulted in increased productivity without, however, interfere with the fresh mass of plants. The cultivars showed similarity in titratable acidity and soluble solids/titratable acidity, soluble solids while for Amelia and Angelina proved superior to Taina. The soluble solids and soluble solids/titratable acidity increased by planting spacing